The Effectiveness of Organizational Communication in Improving Employee Performance at PT. Tirta Sibayakindo - Mardia, Ilham Maulana Admaika; Peranginangin, Indira Fatra Deni (Jurnal Ilmu Komunikasi Dan Media Sosial (JKOMDIS), 2024)
This research aims to determine the effectiveness of organizational communication in improving the performance of PT. Sibayakindo employees. This research uses qualitative descriptive data analysis techniques. The data collection techniques used are observation, documentation and interviews with people and organization development. Based on the research results, it is concluded that communication is what binds the company together. Communicating well in a company is not easy, therefore communication strategies are needed. Organizational communication is the delivery and interpretation of messages between communication units in a particular organization. The main purpose of organizational communication is to convey thoughts, views and opinions, share information, express feelings and emotions, and work together. Organizational communication is not just about sharing information but also about building a strong foundation for progress and success. The strategies created and implemented are quite helpful and facilitate the performance of PT. Tirta Sibayakindo employees.